Business Strategies That Work. A Planning Guide for Education Restructuring. Corporate Action Package - National Alliance of Business, Inc., Washington, DC.; National Alliance of Business, Inc., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This guide is one of a series of publications that the National Alliance of Business is providing to stimulate and sustain U.S. business efforts to restructure public education in order to make it more responsive to the changing requirements of the modern workplace. This publication provides business people with some of the tools that will help them take the critical actions that are needed. It provides two detailed planning guides for businesses, enabling them to plan successfully and structure their involvement in education within broad community coalitions and within their individual companies. Critical elements for success are identified. Case studies illustrate how business can have a substantial impact on education by doing the necessary preparation and planning and following through over the long term. Case studies describe action in South Carolina; Lowndes County, Alabama; Milwaukee, Wisconsin; and Rochester, New York. Thirty-one references are included. (KC)
Availability: National Alliance of Business, 1201 New York Avenue, NW, Suite 700, Washington, DC 20005.
Sponsoring Agency: Department of Labor, Washington, DC.
Sponsoring Agency: Xerox Corp., Rochester, NY.
ERIC Note: For related documents, see ED 308 408 and ED 312 484-487.
Community.
May also be available online. Address as at 14/8/18
Keywords: Business Responsibility; Cooperative Programs; Corporate Support; Educational Change; Educational Improvement; Elementary Secondary Education; Employer Attitudes; Employers; Institutional Cooperation; Leadership Responsibility; Planning; Postsecondary Education; Private Sector; Program Development; School Business Relationship; Vocational Education; Guides, Non-Classroom.